PEDAGOGICAL ASPECTS OF EDUCATION OF FUTURE SPECIALISTS IN PHYSICAL EDUCATION AND SPORTS - Olimov, Alisher (Физическое воспитание, спорт и здоровье, 2023)
This article describes the professional and pedagogical training of specialists in the field of physical culture and sports, the effectiveness of professional aspects, forms and methods of improving professional training, the quality of professional competence and their essence. The necessity of developing innovative special programs for improving professional and pedagogical competence is substantiated, proposals and recommendations on its components are developed, and conclusions are presented.